Physiological Character of Merremia peltata (L.) Merrill from Bukit Barisan Selatan National Park Lampung - Yuke Mardiati; Triadiati Triadiati; Soekisman Tjitrosoedirdjo (Bogor Agricultural University, Indonesia, 2018)
Merremia peltata invaded the vegetation of Bukit Barisan Selatan National Park (BBSNP) in Lampung Province, Indonesia. In this site, the invasion has reached more than 7000 hectares. Therefore, it is necessary to asses the physiological characters of M. peltata as an invasive plant species under different shading level in BBSNP. The experiment design of this study was split block design with factorial. The first factor (main plot) was shading treatment that consisted of 0, 55, and 90% shades. The second factor (sub plot) was 3 species of plant that consisted of M. peltata, Mikania micrantha, and Ipomoea batatas. Each experimental unit was replicated 3 times. The result showed that the physiological characters such as carbon fixation rate (CFR), relative growth rate (RGR), leaf area ratio (LAR), photosynthetics nitrogen use efficiency (PNUE) of M. peltata higher than the other two species and interconnected. Physiological characters associated with RGR can be supporting the invasiveness of M. peltata, especially in BBSNP. Supporting invasiveness with resources allocation to leaves biosynthesis and relatively efficient nitrogen were used for photosynthesis.